Development of aptamer nanoparticles for treatment of retinal diseases - Moreira, David Nabais (2022)
At more advanced states, retinal diseases such as diabetic retinopathy, age-related macular degeneration, and retinal vessel occlusions are characterized by neovascularization, which is usually triggered by a hypoxia episode leading to the overexpression of vascular endothelial growth factor (VEGF) and nucleolin (NCL). The treatments available are mainly corticosteroids or/and antibodies against some angiogenic molecules. Regarding the low efficacy of these therapies and their side effects, aptamers are an emerging tool that can target these proteins with high specificity, such as antibodies. Furthermore, aptamers are easier to synthesize and present higher stability and lower immunogenicity. AT11-L0 is an aptamer derivative of AS1411 composed of G-rich sequences which can adopt G-quadruplex (G4) structure and target NCL, a protein that can act as a co-receptor for several growth factors. Hence, this study aimed to characterize the AT11-L0 structure and its interaction with several ligands (stabilizing molecules or drugs) for NCL targeting. The AT11-L0-drug/molecule complex was then incorporated in a nanoparticle to increase the bioavailability of the aptamer-based drug in the formulation. To achieve these objectives, we have performed biophysical studies, such as nuclear magnetic resonance, circular dichroism, and fluorescence experiments. Following biophysical characterization studies, we synthesised gold nanoparticles and liposomes containing AT11-L0 aptamer-drug complex. Finally, liposomes and the encapsulated drugs were tested on Human umbilical vein endothelial cells (HUVEC) model to assess their antiangiogenic capacity. The results showed that AT11-L0 aptamer-drug complex has a high stability with melting temperatures reaching 45 ºC to 60 ºC allowing an efficient targeting of NCL with a KD in the order of micromolar. HUVEC antiangiogenic assay showed that, although liposomes did not promote an increase in the antiangiogenic effect of the tested drugs, C8 showed an antiangiogenic effect that was not previously described, at lower concentration. This result can be a basis for the development of a new therapeutic approach using C8 and G4 aptamers targeting NCL.